Answer:
x = [tex]\frac{3}{7}[/tex], x = [tex]\frac{-3}{7}[/tex]
Step-by-step explanation:
The first step is to get rid of the square on the x, and to get rid of it, you square root both sides of the equation, like so:
[tex]x^{2} = \frac{9}{49}[/tex]
[tex]\sqrt{x^2} = \sqrt{\frac{9}{49} }[/tex]
A perfect square is when a number has two factors that are identical to one another. In this case, 9 and 49 are both perfect squares, meaning we can break them down:
The square root of 9 is 3. (3 · 3 = 9)
The square root of 49 is 7. (7 · 7 = 49)
x = [tex]\frac{3}{7}[/tex]
The answer is also x = [tex]\frac{-3}{7}[/tex] because a negative · a negative = a positive.